The Relevance of Paulo Freire’s Liberation Education to the Implementation of the Independent Curriculum in Indonesia - Juppenny, Ryan; Cahyono, Hadi; Hudijono, Singkir; Mahardhani, Ardhana Januar (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Education in Paulo Freire's view has a great urgency as a means of liberation from social, political and economic injustice. This article examines the concept of Paulo Freire education which is oriented to humanization and critical awareness (conscienient) to fight dehumanization. Freire rejected the education model